Calibration of an RF/Microwave Phase Noise Meter with a Photonic Delay Line - Andrej Lavrič; Boštjan Batagelj; Matjaž Vidmar (Photonics, 2022)
The main advantage of phase noise meters with photonic (fiber) delay lines is that they do not require high-performance, low-noise reference oscillators. On the other hand, some additional calibrations are required, which are the subject of this paper. First, the quadrature must be maintained on the mixer by precise adjustment of the phase and/or delay. Next, since the response of the mixer is proportional to the square of the input test signal, a precise amplitude calibration is required. Finally, the frequency response of the FFT spectrum analyzer and its corresponding anti-aliasing low-pass filter needs to be known precisely. In this paper, to the best of our knowledge, we present innovative solutions for all three calibrations. All three calibrations were built in and tested in our phase noise meter. The result is a simple and robust phase noise meter suitable for non-laboratory environments.